Management of myelofibrosis after ruxolitinib failure - Harrison, Claire N (Ann Hematol, 2020)
Myelofibrosis is a BCR-ABL1–negative myeloproliferative neoplasm characterized by anemia, progressive splenomegaly, extramedullary hematopoiesis, bone marrow fibrosis, constitutional symptoms, leukemic progression, and shortened survival. Constitutive activation of the Janus kinase/signal transducers and activators of transcription (JAK-STAT) pathway, and other cellular pathways downstream, leads to myeloproliferation, proinflammatory cytokine expression, and bone marrow remodeling. Transplant is the only curative option for myelofibrosis, but high rates of morbidity and mortality limit eligibility. Several prognostic models have been developed to facilitate treatment decisions. Until the recent approval of fedratinib, a JAK2 inhibitor, ruxolitinib was the only available JAK inhibitor for treatment of intermediate- or high-risk myelofibrosis. Ruxolitinib reduces splenomegaly to some degree in almost all treated patients; however, many patients cannot tolerate ruxolitinib due to dose-dependent drug-related cytopenias, and even patients with a good initial response often develop resistance to ruxolitinib after 2–3 years of therapy. Currently, there is no consensus definition of ruxolitinib failure. Until fedratinib approval, strategies to overcome ruxolitinib resistance or intolerance were mainly different approaches to continued ruxolitinib therapy, including dosing modifications and ruxolitinib rechallenge. Fedratinib and two other JAK2 inhibitors in later stages of clinical development, pacritinib and momelotinib, have been shown to induce clinical responses and improve symptoms in patients previously treated with ruxolitinib. Fedratinib induces robust spleen responses, and pacritinib and momelotinib may have preferential activity in patients with severe cytopenias. Reviewed here are strategies to ameliorate ruxolitinib resistance or intolerance, and outcomes of clinical trials in patients with myelofibrosis receiving second-line JAK inhibitors after ruxolitinib treatment.